Changes in the Incidence of Invasive Bacterial Disease During the COVID-19 Pandemic in the United States, 2014–2020. (1st February 2023) - Prasad, Namrata; Rhodes, Julia; Deng, Li; McCarthy, Natalie L; Moline, Heidi L; Baggs, James; Reddy, Sujan C; Jernigan, John A; Havers, Fiona P; Sosin, Daniel M; Thomas, Ann; Lynfield, Ruth; et al.
Abstract: Background: Descriptions of changes in invasive bacterial disease (IBD) epidemiology during the coronavirus disease 2019 (COVID-19) pandemic in the United States are limited. Methods: We investigated changes in the incidence of IBD due to Streptococcus pneumoniae, Haemophilus influenzae, group A Streptococcus (GAS), and group B Streptococcus (GBS). We defined the COVID-19 pandemic period as 1 March to 31 December 2020. We compared observed IBD incidences during the pandemic to expected incidences, consistent with January 2014 to February 2020 trends. We conducted secondary analysis of a health care database to assess changes in testing by blood and cerebrospinal fluid (CSF) culture during the pandemic. Results: Compared with expected incidences, the observed incidences of IBD due to S. pneumoniae, H. influenzae, GAS, and GBS were 58%, 60%, 28%, and 12% lower during the pandemic period of 2020, respectively. Declines from expected incidences corresponded closely with implementation of COVID-19–associated nonpharmaceutical interventions (NPIs). Significant declines were observed across all age and race groups, and surveillance sites for S. pneumoniae and H. influenzae. Blood and CSF culture testing rates during the pandemic were comparable to previous years. Conclusions: NPIs likely contributed to the decline in IBD incidence in the United States in 2020; observed declines were unlikely to be driven by reductions in testing. Abstract : COVID-19–associated nonpharmaceutical interventions likely contributed to the decline in invasive bacterial disease incidence in the United States in 2020; observed declines were unlikely to be driven by reductions in testing.